2016
DOI: 10.1002/cpt.393
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Projection of First‐in‐Human Dose for Bispecific Immunomodulatory P‐Cadherin LP‐DART: An Integrated PK/PD Modeling Approach

Abstract: A bispecific immunomodulatory biotherapeutic molecule (P-cadherin LP-DART) based on the Dual Affinity Re-Targeting (DART) scaffold has been developed as a potential antitumor treatment showing efficacy in preclinical testing. A minimal anticipated biological effect level (MABEL) approach was applied to project the first-in-human (FIH) dose, because of its immune agonistic properties following target engagement. The pharmacological activity of P-cadherin LP-DART is driven by binding to both P-cadherin on the tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(48 citation statements)
references
References 25 publications
1
47
0
Order By: Relevance
“…Similarly, the proposed TBE model was able to simultaneously capture the reported in vitro cytotoxicity time course of an extended half-life Dual Affinity Re-Targeting scaffold bispecific directed against CD3 and P-cadherin (P-cadherin LP-DART)-mediated P-cadherin+ HCT116 tumor cell killing by peripheral blood mononuclear cells (PBMCs) at various E:T ratios, 16 suggesting broader applications of the proposed TBE model. Results of the P-cadherin LP-DART modeling are provided in Supplement Materials (Table S1 and Figure S1).…”
Section: Resultsmentioning
confidence: 83%
See 4 more Smart Citations
“…Similarly, the proposed TBE model was able to simultaneously capture the reported in vitro cytotoxicity time course of an extended half-life Dual Affinity Re-Targeting scaffold bispecific directed against CD3 and P-cadherin (P-cadherin LP-DART)-mediated P-cadherin+ HCT116 tumor cell killing by peripheral blood mononuclear cells (PBMCs) at various E:T ratios, 16 suggesting broader applications of the proposed TBE model. Results of the P-cadherin LP-DART modeling are provided in Supplement Materials (Table S1 and Figure S1).…”
Section: Resultsmentioning
confidence: 83%
“…This simplification was implemented partly because the in vitro cytotoxicity data that were available for model development and validation were all obtained within 96 hours of incubation, and no significant T cell proliferation is expected within 48–96 hours of incubation. 16,55 In addition, an ex vivo cytotoxicity experiment using acute myeloid leukemia patient samples showed that, in patient samples with E:T ratios < 1:10, addition of either anti-programmed cell death 1 (PD-1) or anti- programmed cell death ligand 1 (PD-L1) antibodies significantly augmented AMG 330-induced target cell lysis. In patient samples with E:T ratios > 1:10, the enhancement effect of anti-PD-1 or anti-PD-L1 antibodies on AMG 330-induced target cell lysis was limited, suggesting that the upregulation of PD-1/PD-L1 may be minor at higher E:T ratios (e.g., > 1:10).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations